Risk factors associated with death in Brazilian children with severe dengue: a case-control study (Clinics, 2014)
Objective: The purpose of this case-control study was to evaluate risk factors associated with death in children with severe dengue. Methods: The clinical condition of hospitalized patients with severe dengue who died (cases, n = 18) was compared with that of hospitalized patients with severe dengue who survived (controls, n = 77). The inclusion criteria for this study were age under 13 years; hospital admission in São Luis, northeastern Brazil; and laboratory-confirmed diagnosis of dengue. Results: Severe bleeding (hemoptysis), a defining criterion for dengue severity, was the factor most strongly associated with death in our study. We also found that epistaxis and persistent vomiting, both included as warning signs in the World Health Organization (WHO) classification of dengue, were strongly associated with death. No significant association was observed between any of the laboratory findings and death. Conclusions: The finding that epistaxis and persistent vomiting were also associated with death in children with severe dengue was unexpected and deserves to be explored in future studies. Because intensive care units are often limited in resource-poor settings, any information that can help to distinguish patients with severe dengue with a higher risk to progress to death may be crucial.